Highly-crystalline lanthanide doped and carbon encapsulated Li4Ti5O12 nanosheets as an anode material for sodium ion batteries with superior electrochemical performance. (20th July 2016) - Wu, Z.L.; Xu, G.B.; Wei, X.L.; Yang, L.W.
Graphical abstract: Highly-crystalline lanthanide doped and carbon encapsulated Li4 Ti5 O12 nanosheets as an anode material for sodium ion batteries with superior electrochemical performance are demonstrated. Abstract: Highly-crystalline lanthanide (Ln 3+ = Gd 3+, Y 3+ and La 3+ ) doped and carbon encapsulated Li4 Ti5 O12 (designated as C-Ln-LTO) nanosheets as an anode material for sodium ion batteries (NIBs) are synthesized on large scale via a facile hydrothermal reaction followed by annealing treatment. When evaluated as an anode material for NIBs, the C-Ln-LTO nanosheets exhibit initial discharge specific capacity of 198 mA h g −1 at 0.1C, enhanced rate capability of 141 mA h g −1 at 2C and superior cyclic performance of 122 mA h g −1 at 2C after 150 cycles. The superior rate capability and cyclic performance benefit from the synergistic effect of Ln 3+ doping and carbon encapsulation, which promote electrode reaction kinetics and structural stability during Na + insertion/extraction. Our results reveal the feasibility and universality that the combination of carbon encapsulation and Ln 3+ doping improves electrochemical performance of LTO-based anode materials for rechargeable high-performance NIBs.